2021
DOI: 10.1063/5.0066698
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of metastable dual-phase (Ti0.25V0.25Zr0.25Hf0.25)B2 to stable high-entropy single-phase boride by thermal annealing

Abstract: Transition metal borides have a unique combination of high melting point and high chemical stability and are suitable for high temperature applications (>2000 °C). A metastable dual-phase boride (Ti0.25V0.25Zr0.25Hf0.25)B2 with distinct two hexagonal phases and with an intermediate entropy formation ability of 87.9 (eV/atom)−1 as calculated via the density functional theory (DFT) was consolidated by pulsed current sintering. Thermal annealing of the sintered dual-phase boride at 1500 °C promoted the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…These impurities get impregnated during material synthesis, typically via mechanical alloying and sintering of metal oxides in the presence of B 4 C. Monitoring and precise control of the proportion of such impurities is challenging; hence, estimating the hardness of a pure single-phase material devoid of grain boundary segregations is difficult and requires optimal synthesis methods that minimize exposure to oxide and carbonaceous contents. 14,24,[28][29][30][31]43 A widely reported multicomponent boride (Hf 0.2 Zr 0.2 Ta 0.2 Nb 0.2 Ti 0.2 )B 2 has been reported to possess hardness between 16.4 and 25.4 GPa from experimental measurements, 14,21,22,24,29,31,44−46 with its single phase chemistry assuming 16.4 46 and 20.9 GPa 43 per the literature. Similarly, the hardness of another multicomponent boride (Hf 0.2 Zr 0.2 Ti 0.2 Ta 0.2 Cr 0.2 )B 2 is recorded to range from 19.9 to 29.3 GPa, while its single-phase structures have a hardness between 19.9 and 25.4 GPa.…”
Section: ■ Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…These impurities get impregnated during material synthesis, typically via mechanical alloying and sintering of metal oxides in the presence of B 4 C. Monitoring and precise control of the proportion of such impurities is challenging; hence, estimating the hardness of a pure single-phase material devoid of grain boundary segregations is difficult and requires optimal synthesis methods that minimize exposure to oxide and carbonaceous contents. 14,24,[28][29][30][31]43 A widely reported multicomponent boride (Hf 0.2 Zr 0.2 Ta 0.2 Nb 0.2 Ti 0.2 )B 2 has been reported to possess hardness between 16.4 and 25.4 GPa from experimental measurements, 14,21,22,24,29,31,44−46 with its single phase chemistry assuming 16.4 46 and 20.9 GPa 43 per the literature. Similarly, the hardness of another multicomponent boride (Hf 0.2 Zr 0.2 Ti 0.2 Ta 0.2 Cr 0.2 )B 2 is recorded to range from 19.9 to 29.3 GPa, while its single-phase structures have a hardness between 19.9 and 25.4 GPa.…”
Section: ■ Resultsmentioning
confidence: 94%
“…Most multicomponent borides have heterogeneities consisting of B 4 C, graphite, (Zr/Hf)­O 2 , and segregates of unitary or mixed-phase borides. These heterogeneities emerge at grain boundaries and improve the structural properties relative to those of their single-phase counterparts. These impurities get impregnated during material synthesis, typically via mechanical alloying and sintering of metal oxides in the presence of B 4 C. Monitoring and precise control of the proportion of such impurities is challenging; hence, estimating the hardness of a pure single-phase material devoid of grain boundary segregations is difficult and requires optimal synthesis methods that minimize exposure to oxide and carbonaceous contents. ,, , A widely reported multicomponent boride (Hf 0.2 Zr 0.2 Ta 0.2 Nb 0.2 Ti 0.2 )­B 2 has been reported to possess hardness between 16.4 and 25.4 GPa from experimental measurements, ,,,,,, with its single phase chemistry assuming 16.4 and 20.9 GPa per the literature. Similarly, the hardness of another multicomponent boride (Hf 0.2 Zr 0.2 Ti 0.2 Ta 0.2 Cr 0.2 )­B 2 is recorded to range from 19.9 to 29.3 GPa, while its single-phase structures have a hardness between 19.9 and 25.4 GPa. ,,, A case in point is that single-phase multicomponent borides have a lower hardness relative to their precursor metal diborides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have been dedicated to this topic [6,12]. TE investigations of non-oxide HE ceramics like borides [14][15][16][17] or carbides [18][19][20] have been limited and most studies have only speculated about the effects. Computational studies suggest that the compositional diversity may affect TE [15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies suggest that the compositional diversity may affect TE [15,20]. However, experimental studies of the TE of HE borides and carbides remain sparse at best [15][16][17]. Iwan et al investigated the equation of state of (Hf,Nb,Ta,Ti,Zr)B 2 up to 2000 K 14 and found a non-linear volumetric thermal expansion with coefficients…”
Section: Introductionmentioning
confidence: 99%